2003
DOI: 10.1017/s0952523803204107
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of TRPC channel subunits 1 and 4 in the chicken retina

Abstract: In the vertebrate retina, multiple cell types express G protein-coupled receptors linked to the IP3 signaling pathway. The signaling engendered by activation of this pathway can involve activation of calcium permeable transient receptor potential (TRP) channels. To begin to understand the role of these channels in the retina, we undertake an immunocytochemical localization of two TRP channel subunits. Polyclonal antibodies raised against mammalian TRPC1 and TRPC4 are used to localize the expression of these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
(93 reference statements)
2
22
0
Order By: Relevance
“…These structures contain neuronal cells appearing early on the second day post-fertilization (Hu and Easter, 1999). This is consistent with the general role of TRPC channels in sensory physiology (Montell, 1997), and the previously reported immunolocalization of TRPC1 in the chicken retina (Crousillac et al, 2003). …”
supporting
confidence: 74%
“…These structures contain neuronal cells appearing early on the second day post-fertilization (Hu and Easter, 1999). This is consistent with the general role of TRPC channels in sensory physiology (Montell, 1997), and the previously reported immunolocalization of TRPC1 in the chicken retina (Crousillac et al, 2003). …”
supporting
confidence: 74%
“…In chicken retina, immunoreactivity for TRPC1 and TRPC4 was identified, with TRPC1 staining localized to the inner plexiform layer and TRPC4 labeling more extensively distributed to all layers of the retina, including Müller cells. 40 Examination of Ca 2ϩ entry pathways in mouse retina suggested that TRPC6 may operate as a putative store-operated Ca 2ϩ channel in the cell body of rods, and TRPC6 immunoreactivity was also observed in the cell bodies of bipolar, amacrine, and retinal ganglion cells. 34 More recently, study 41,42 of the light-activated signaling pathway in rat suprachiasmatic nuclei-projecting retinal ganglion cells has provided additional evidence supporting the involvement of a G-protein-mediated signaling pathway and activation of a TRP-like cation current.…”
Section: Discussionmentioning
confidence: 98%
“…A number of polyclonal (Wang et al 1999;Bobanovic et al 1999;Brereton et al 2000;Rosado and Sage 2000;Xu and Beech 2002;Goel et al 2002;Crousillac et al 2003;Goel et al 2006) and monoclonal (Tsiokas et al 1999) antibodies which recognise the TRPC1 polypeptide have been developed and employed in studies This table combines data obtained using a number of different techniques and cell types, and endogenous and ectopically expressed TRPC1. Further experiments are required to confirm that, for some proteins in the list, the interaction with TRPC1 occurs in vivo, to elucidate the functional consequences of this interaction, and the cell types in which this occurs of TRPC1 function.…”
Section: Antibodies Against Trpc1mentioning
confidence: 98%
“…The results of several studies, chiefly employing immunofluorescence, have identified those cell types in a particular organ in which TRPC1 is expressed. These include neurons (Goel et al 2002;Glazebrook et al 2005;von Bohlen-Und-Halbach et al 2005) the retina (Crousillac et al 2003) and kidney (Goel et al 2006). …”
Section: Expression Of Trpc1 In Tissues and Cellsmentioning
confidence: 98%